Psychology in Human Resource Management - Suniyah Nur Fahmi; Hanna Aqeela Humayra; Mochamad Aqshal Saliim; Cindy Tiara Adinda; Arfian Arfian (Socrates: Journal of Education, Philosophy and Psychology, 2025)
This review examines the role of psychology in human resource management (HRM) by emphasizing how principles from Industrial and Organizational Psychology (I/O Psychology) enhance the quality of employee management. Using a literature review approach, the discussion focuses on key HRM functions such as recruitment and selection, training and development, work motivation, performance appraisal, and employee well-being. The findings indicate that psychological approaches improve the objectivity of selection processes, the effectiveness of training transfer, intrinsic motivation, and fairness in performance evaluation systems. The integration of psychological principles also contributes to higher productivity, job satisfaction, and employee retention through the fulfillment of psychological needs, perceived organizational support, and a healthy work environment. These insights highlight that applying psychological principles within HRM is a strategic element for building organizations that are adaptive, sustainable, and oriented toward human well-being.